Circus movement atrial flutter in the canine sterile pericarditis model: relation of characteristics of the surface electrocardiogram and conduction properties of the reentrant pathway - Schöls, Wolfgang; Offner, Bertram; Brachmann, Johannes; Kübler, Wolfgang; El-Sherif, Nabil (Journal of the American College of Cardiology, 1994)
Objectives. This study was designed to elucidate the basis for the electrocardiographic (ECG) appearance of atrial flutter in the canine sterile pericarditis model. Background. During atrial flutter, the surface ECG may show typical F waves or isolated P waves of any polarity. Methods. Electrocardiographic leads II, III and aVF and epicardial atrial activation maps constructed from 127 simultaneously recorded bipolar electrograms were compared in 20 dogs with sterile pericarditis and inducible atrial flutter. Results. In 10 dogs with F wave atrial flutter, single loop reentry occurred around combined functional/anatomic obstacles that included one or both caval veins and a vertically oriented arc of functional conduction block. In 10 dogs with P wave atrial flutter, a merely functional (n = 4) or combined (n = 6) obstacle involving any atrial vessel and more vertically (n = 5) or more horizontally (n = 5) oriented arcs of block was present. The isoelectric interval between P waves corresponded to the conduction time within the slow zone of the reentrant circuit (96 ± 27 vs. 100 ± 24 ms, mean ± SD). Slow conduction accounted for 65 ± 8% of the cycle length in P wave atrial flutter, but for only 29 ± 7% in F wave atrial flutter (p < 0.05). Slow conduction was usually associated with activation of fewer than five epicardial electrodes per 10-ms isochronal interval, reflecting only a small amount of atrial tissue. The polarity of P or F waves was determined by the direction of the major wave front activating the most electrodes per 10-ms isochronal interval, irrespective of whether the right or the left atrium was activated. Conclusions. The F waves result from reentrant activation at a relatively constant speed around a vertically oriented functional/ anatomic obstacle involving one or both caval veins. The P waves occur when the circuit contains a marked area of slow conduction.
Elektronische Reproduktion der Druck-Ausgabe 29. März 2004
Gesehen am 23.05.2024